RADIOGRAPHY OF OS HUMERUS SINISTRA WITH SUSPENSION MULTIPLE FRACTURES OF THE MIDDLE 1/3 OF THE HUMERUS AT THE Drs. H. AMRI TAMBUNAN LUBUK PAKAM REGIONAL HOSPITAL - Helvinus Laia; Liberti Tarigan (Yayasan Nuraini Ibrahim Mandiri, 2025)
The humerus is the longest and largest bone in the upper extremity. It articulates proximally with the scapula and distally with the elbow or antebrachium. The proximal end of the humerus has a rounded head (caput humeri) that articulates with the glenoid cavity of the scapula to form the glenohumeral joint. Distal to the humeral head is the anatomical neck, which appears as an oblique groove. Distal to the anatomical neck is the greater tubercle. The greater tubercle is the most palpable lateral landmark of the humerus in the shoulder region. Between the greater tubercle and the lesser tubercle is a groove called the intertubercular sulcus. The primary function of the humerus is to provide attachment for arm muscles and support various physical functions of the arm. A fracture is a condition in which the continuity of bone and cartilage is disrupted due to impact or osteoporosis. Multiple fractures are a condition in which the continuity of bone tissue is lost in more than one line. This study aims to produce an optimal radiographic image of the left humerus with suspected Multiple Fractures of the Middle 1/3 of the Humerus, so that the photo results can be used as accurate results for further treatment. This study was conducted at the Radiology Installation of Drs. H. Amri Tambunan Regional General Hospital, the research time was in April 2025, the research method used was the interview method, and direct observation. Examination of the left humerus with suspected Multiple Fractures of the Middle 1/3 of the Humerus was carried out using Antero-Posterior and Lateral projections. In this examination the author used a general X-ray unit, with the image recording process using digital radiography (DR).